The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1590/pboci.2022.006
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Frequency of Occupational Hazards Among a Group of Iranian General Dentists and its Prevention Criteria

Abstract: Objective: To evaluate the frequency of occupational hazards and the criteria for their prevention among Iranian dentists. Material and Methods: This cross-sectional study was conducted on 187 general dentists in Kerman. The data collection tool was a questionnaire including personal information (gender, age, marital status, condition and place and years of employment, and the average of weekly working hours) and a valid and reliable questionnaire of occupational hazards, including 24 questions about occupatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
2
0
0
Order By: Relevance
“…A larger proportion of injured workers is married or in a long-term relationship. This result supports the results of previous studies which indicate that the married population usually has a lower risk of suffering serious accidents but a higher incidence of minor accidents (Afshar et al 2022;Farahbod et al 2021;Saranjam et al 2020). This may be related to other variables such as impulsivity (ability to maintain stable relationships) or age (the longer the relationship, the older).…”
Section: Discussionsupporting
confidence: 92%
“…A larger proportion of injured workers is married or in a long-term relationship. This result supports the results of previous studies which indicate that the married population usually has a lower risk of suffering serious accidents but a higher incidence of minor accidents (Afshar et al 2022;Farahbod et al 2021;Saranjam et al 2020). This may be related to other variables such as impulsivity (ability to maintain stable relationships) or age (the longer the relationship, the older).…”
Section: Discussionsupporting
confidence: 92%
“…This result is inconsistent with the findings of another study carried by Afshar MK in which they found no statistical significance relationship between marital status & the employees' knowledge on occupational hazards. [12] In addition, the current study findings also congruent with study that conducted by Sabita and others (2018) who reported that no association among marital status with level of knowledge on occupational health hazards at p-value 0.45 [13] Table 4 The relationship between marital status and employees' knowledge on the occupational hazards…”
Section: Resultssupporting
confidence: 90%